Svarganuṃ sāhitya pīrasanāra Amrtalāla Paḍhiyāra - Vahorā, Rasūlabhāī Na. (Rasūlabhāī Nabījī), 1902-1958 (SAMP early 20th-century Indian books project, 1940)
Biography of Amrtalāla Sundarajī Paḍhiyāra, 1870-1919, Hindu religious leader from Gujarat.